The law of nations and the United States Constitution - Bellia, Anthony J., Jr; Clark, Bradford R. (New York, NY : Oxford University Press, 2017)
'The Law of Nations and the United States Constitution' offers a new lens through which anyone interested in constitutional governance in the United States should analyze the role and status of customary international law in U.S. courts. The work explains that the law of nations has not interacted with the Constitution in any single overarching way. Rather, the Constitution was designed to interact in distinct ways with each of the three traditional branches of the law of nations that existed when it was adopted-namely, the law merchant, the law of state-state relations, and the law maritime.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 15, 2017).
Keywords: Constitutional law -- United States; Customary law, International; Law; Laws of specific jurisdictions & specific areas of law